Study-Aid Books, Workbooks, and IT Equipment as New Materials for School Students in Japanese Public Libraries - Tsuji, Keita (UI Scholars Hub, 2022)
Japan is no longer a rich country. The poverty rate for “a single adult household with at least one child” is the third highest among the 44 countries of OECD. Public libraries should provide study-aid books, workbooks, and IT equipment to poor students. Based of this idea, we first identified 129 study-aid books and workbooks for junior high and high school students. Next, we investigated whether public libraries of all 1,392 Japanese local governments held them. Then, we asked 631 students whether they wanted public libraries to hold the books and IT equipment such as Nintendo Switch and iPad. Furthermore, we gathered three students, provided books and IT equipment, and asked whether they wanted public libraries to hold them. It was shown that poor students wanted public libraries to have study-aid books and workbooks for English. Video games were desired by many students. Japanese public libraries should consider providing them.